2016
DOI: 10.1007/s10936-016-9427-1
|View full text |Cite
|
Sign up to set email alerts
|

How Linearity and Structural Complexity Interact and Affect the Recognition of Italian Derived Words

Abstract: The majority of words in most languages consist of derived poly-morphemic words but a cross-linguistic review of the literature (Amenta and Crepaldi in Front Psychol 3:232-243, 2012) shows a contradictory picture with respect to how such words are represented and processed. The current study examined the effects of linearity and structural complexity on the processing of Italian derived words. Participants performed a lexical decision task on three types of prefixed and suffixed words and nonwords differing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 101 publications
(230 reference statements)
2
4
1
Order By: Relevance
“…We found significant priming effects with both prefixed and suffixed words. This finding indicates efficient morphological decomposition for both prefixed words and suffixed words, which seems to contradict claims made in the literature that prefixed words might be less susceptible to decomposition than suffixed ones (Beauvillain, 1996;Bergman et al, 1988;Colé et al, 1989;Ferrari Bridgers & Kacinik, 2017). However, all these prior studies have employed experimental techniques in which stimuli were overtly presented for lexical decision, which may explain why these studies yielded different results from the masked priming experiments testing existing prefixed words (Diependaele et al, 2009;Forster & Azuma, 2000;Grainger et al, 1991;Heide et al, 2010;Kim et al, 2015).…”
Section: Summary Of Findingscontrasting
confidence: 60%
See 1 more Smart Citation
“…We found significant priming effects with both prefixed and suffixed words. This finding indicates efficient morphological decomposition for both prefixed words and suffixed words, which seems to contradict claims made in the literature that prefixed words might be less susceptible to decomposition than suffixed ones (Beauvillain, 1996;Bergman et al, 1988;Colé et al, 1989;Ferrari Bridgers & Kacinik, 2017). However, all these prior studies have employed experimental techniques in which stimuli were overtly presented for lexical decision, which may explain why these studies yielded different results from the masked priming experiments testing existing prefixed words (Diependaele et al, 2009;Forster & Azuma, 2000;Grainger et al, 1991;Heide et al, 2010;Kim et al, 2015).…”
Section: Summary Of Findingscontrasting
confidence: 60%
“…Hasenäcker, Schröter, and Schroeder (2017) found that children show effects of morphological decomposition for prefixed words later than for suffixed words. For L1 adults, Ferrari Bridgers and Kacinik (2017) reported that prefixed words take longer to process than suffixed words. Likewise, Bergman, Hudson, and Eling (1988) showed that lexical decision times in response to suffixed and pseudosuffixed words are similar, but pseudoprefixed words take longer to recognize than prefixed words, which suggests that stem access is automatic only in suffixed words.…”
Section: Background Literaturementioning
confidence: 99%
“…This dissociation between prefixed and suffixed words can only be explained by positing that, at some level of processing, the relative position of affix and stem influences how prefixed and suffixed words are processed and retrieved. This is in line with previous results from psycholinguistic studies that have reported larger processing costs for prefixed as compared to suffixed words, which the authors explained in terms of more effortful access to the stem when this is in word-final position (Bergman et al, 1988;Colé et al, 1989;Beauvillain, 1996;Ferrari Bridgers and Kacinik, 2017). We FIGURE 1 | Mean accuracy in the production of initial syllables (or prefixes) and final syllables (or suffixes) in the three conditions, for each PwA across all trials.…”
Section: Discussionsupporting
confidence: 91%
“…In line with the typical profile of a morphological impairment (e.g., Job and Sartori, 1984;Rastle et al, 2006;Lorenz and Zwitserlood, 2014), we expected both prefixed and suffixed words to yield more errors than simple words. However, if it is true that processing prefixed words is more costly than processing suffixed words because of the word-final position of the stem (Bergman et al, 1988;Colé et al, 1989;Beauvillain, 1996;Ferrari Bridgers and Kacinik, 2017), then prefixed words may be more impaired than suffixed words. We then focused on the types of errors produced, and specifically on the likelihood of producing an error specifically affecting the prefix or the suffix.…”
Section: The Present Studymentioning
confidence: 99%
“…di+kgeleke, bo +kgeleke) by which the base stem is isolated and directly primes the target stem. Thus, while the processing of prefixed words may somehow incur extra effort compared to suffixed words, as suggested by unprimed lexical decision and eye-tracking studies (Beauvillain, 1996;Bergman et al, 1988;Colé et al, 1989;Ferrari Bridgers & Kacinik, 2017), the purportedly disadvantageous word-final position of the stem within a prefixed word form does not preclude reliable morphological priming.…”
Section: Discussionmentioning
confidence: 99%